The cultural heritage – a matter of training (Research Announcements "Heritage BG", 2025)
In this article, the author discusses the endeavor for a revival of past traditions and for their safeguarding in our contemporary world. What we call cultural heritage is not heritage strictly speaking, but an invented tradition, which we assimilate with certain alteration from the past in order to fit the present and its problems. Outlined is the decisive role of the researchers for defining and safeguarding the cultural heritage, as well as for interpreting it and transmitting it to the next generations through developing institutional policies and educational programs.  References:Angelov 1988: Angelov, Angel Valentinov. Razmishlenia varhu traditsiata. – Literaturna misal, №. 10, 71-79. Also in: https://www.academia.edu/25882917/Размишление_върху_традицията (last visited 06.04.2021)Georgieva 2020: Georgieva, Albena. Opazvaneto na traditsiite – znachim aktsent v globalniya svyat. – In: Nina Debryune, Dzheni Madzharov (eds.). Nematerialnoto kulturno nasledstvo – samobitnost, priemstvenost, oporochavane. Sofia: Academic Publishers ‘Za bukvite – O pismeneh’, 10-22.Georgieva, Angelov 1987: Georgieva, Albena, Angelov, Angel. Za neobhodimostta ot teoriya. – Balgarski folklor, № 3, 39-48.Nalbantyan-Hacheryan 2019: Nalbantyan-Hacheryan, Silva. Nematerialno kulturno nasledstvo – politiki i praktiki za negovoto opazvane. Sofia: AP ‘Prof. Marin Drinov’.Zakon 2009: Zakon za kulturnoto nasledstvo: https://www.academia.edu/29734440/ЗАКОН_ЗА_КУЛТУРНОТО_НАСЛЕДСТВО (in Bulgarian, last visited 06.07.2021). http://mc.government.bg/page.php?p=289&s=0&sp=0&t=0&z=0 (in English, last visited 06.07.2021)Georgieva 2017: Georgieva, Albena. Safeguarding the Intangible Cultural Heritage in Bulgaria. – In: Intangible Cultural Heritage: Safeguarding Experiences in Central and Eastern European Countries and China. The 10th Anniversary of the Entry into Force of the 2003 Convention through the Prism of Sustainable Development, ed. by Hanna Shreiber. Warszawa: National Heritage Board of Poland, 2017, 238-253.Convention 2003: Convention for the Safeguarding of the Intangible Cultural Heritage: https://ich.unesco.org/en/convention (in English, last visited 03.07.2021); http://www.unesco-centerbg.org/wp-new/wp-content/uploads/2016/01/Convention-2003-BG.pdf (In Bulgarian, last visited 09.04.2021).Hobsbawm 1983: Hobsbawm, Eric. Introduction: Inventing Traditions. – In: The Invention of Tradition, Eric Hobsbawm and Terence Ranger (eds.). Cambridge University Press, 1-14.
Keywords: tradition; safeguarding; transmission; researcher; cultural policies; educational programs